2014
DOI: 10.1002/ijc.28774
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: miR‐145 sensitizes ovarian cancer cells to paclitaxel by targeting Sp1 and Cdk6

Abstract: Multidrug resistance (MDR) remains a major obstacle to effective chemotherapy treatment in ovarian cancer. In our study, paclitaxel-resistant ovarian cancer patients and cell lines had decreased miR-145 levels and expressed high levels of Sp1 and Cdk6. Introducing miR-145 into SKOV3/PTX and A2780/PTX cells led to a reduction in Cdk6 and Sp1 along with downregulation of P-gp and pRb. These changes resulted in increased accumulation of antineoplastic drugs and G1 cell cycle arrest, which rendered the cells more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 43 publications
5
71
2
Order By: Relevance
“…In ovarian tumors, it is also shown that some cyclindependent kinases (CDK2, CDK4, CDK6, CDK12) were closely related to the survival and therapy for ovarian cancer patients [13][14][15][16]. Moreover, in several human cancers, the role of CDK1 has been well characterized.…”
Section: Discussionmentioning
confidence: 97%
“…In ovarian tumors, it is also shown that some cyclindependent kinases (CDK2, CDK4, CDK6, CDK12) were closely related to the survival and therapy for ovarian cancer patients [13][14][15][16]. Moreover, in several human cancers, the role of CDK1 has been well characterized.…”
Section: Discussionmentioning
confidence: 97%
“…miR-145 targeting of MDR1 helps to restore drug efficacy in resistant cells and in vivo models of bladder cancer and BC (200, 201). Moreover miR-145 confirmed its role in reducing chemoresistance also with paclitaxel (202) and doxorubicin (203), possibly via regulation of EMT.…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 89%
“…Paclitaxel is used to treat a number of solid cancers that include lung, ovarian, breast and pancreatic tumors (308). A number of studies produced evidence that loss of non-coding RNAs regulation can modify chemoresistance to taxol (202, 309313). miR-182 is often up-regulated in cancers; it can enhance cell proliferation, invasion and it plays an important role in drug resistance.…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…miR-145, miR-133a, miR-133b, miR-22 and miR-335 serve an important role in the biology of gastric cancer by regulating SP1 directly (41)(42)(43). miR-145 was also found to regulate SP1 in ovarian cancer cells sensitized to paclitaxel (44). In esophageal carcinoma, Wang et al (45) found that ectopic miR-429 suppressed cell invasion and induced cell apoptosis via the blockade of SP1.…”
Section: Discussionmentioning
confidence: 99%